Alarming decline of freshwater trigger species in western Mediterranean key biodiversity areas. Issue 5 (6th August 2021) - Nogueira, Joana Garrido; Sousa, Ronaldo; Benaissa, Hassan; De Knijf, Geert; Ferreira, Sónia; Ghamizi, Mohamed; Gonçalves, Duarte V.; Lansdown, Richard; Numa, Catherine; Prié, Vincent; Riccardi, Nicoletta; Seddon, Mary; et al.
Abstract: Theidentification of key biodiversity areas (KBA) was initiated by the International Union for Conservation of Nature in 2004 to overcome taxonomic biases in the selection of important areas for conservation, including freshwater ecosystems. Since then, several KBAs have been identified mainly based on the presence of trigger species (i.e., species that trigger either the vulnerability and or the irreplaceability criterion and thus identify a site as a KBA). However, to our knowledge, many of these KBAs have not been validated. Therefore, classical surveys of the taxa used to identify freshwater KBAs (fishes, molluscs, odonates, and aquatic plants) were conducted in Douro (Iberian Peninsula) and Sebou (Morocco) River basins in the Mediterranean Biodiversity Hotspot. Environmental DNA analyses were undertaken in the Moroccan KBAs. There was a mismatch between the supposed and actual presence of trigger species. None of the trigger species were found in 43% and 50% of all KBAs surveyed in the Douro and Sebou basins, respectively. Shortcomings of freshwater KBA identification relate to flawed or lack of distribution data for trigger species. This situation results from a misleading initial identification of KBAs based on poor (or even inaccurate) ecological information or due to increased human disturbance between initial KBA identification and the present. To improve identification of future freshwater KBAs, we suggest selecting trigger species with a more conservative approach; use of local expert knowledge and digital data (to assess habitat quality, species distribution, and potential threats); consideration of the subcatchment when delineating KBAs boundaries; thoughtful consideration of terrestrial special areas for conservation limits; and periodic field validation. Abstract : Article impact statement : The delineation of some KBAs and their focal areas has shortcomings related to flawed data or lack of distribution data for trigger species. Abstract : Alarming decline of freshwater trigger species in western Mediterranean Key Biodiversity Areas Resumen: La identificación de las áreas clave de biodiversidad (ACB) fue iniciada por la Unión Internacional para la Conservación de la Naturaleza en 2004 con el objetivo de sobreponerse a los sesgos taxonómicos en la selección de áreas importantes para la conservación, incluyendo los ecosistemas de agua dulce. Desde entonces, varias ACB han sido identificadas principalmente con base en la presencia de especies desencadenantes (es decir, especies que desencadenan el criterio de vulnerabilidad o de carácter irremplazable y por lo tanto identifican a un sitio como una ACB). Sin embargo, a nuestro conocimiento, muchas de estas ACB no han sido validadas. Por lo tanto, los censos clásicos de taxones utilizados para identificar las ACB de agua dulce (peces, moluscos, odonatos y plantas acuáticas) fueron realizados en las cuencas de los ríos Duero (Península Ibérica) y Sebou (Marruecos) en el Punto Caliente de Biodiversidad del Mediterráneo. Realizamos análisis de ADN ambiental en las ACB de Marruecos. Hubo una discrepancia entre la supuesta presencia y la actual presencia de especies desencadenantes. Ninguna de las especies desencadenantes se encontró en 43% y 50% de las ACB censadas en las cuencas del Duero y del Sebou, respectivamente. Las deficiencias en la identificación de las ACB de agua dulce están relacionadas con la carencia de datos o datos erróneos sobre la distribución de las especies desencadenantes. Esta situación resulta en una identificación inicial engañosa de las ACB con base en información ecológica deficiente (o incluso incorrecta) o también puede deberse al incremento en las perturbaciones humanas ocurridas entre la identificación de la ACB y el presente. Para mejorar la identificación de ACB de agua dulce en el futuro, sugerimos que la selección de especies desencadenantes se realice con un enfoque más conservador; que se usen el conocimiento local de los expertos y los datos digitales (para evaluar la calidad del hábitat, la distribución de las especies y las amenazas potenciales); que se consideren las subcuencas cuando se delimiten las fronteras de las ACB; que se consideren cuidadosamente las áreas de especies terrestres para los límites de conservación; y que se realicen validaciones periódicas de campo.